Analysis of an Induction Machine by the Finite Element Method - Kuczmann, Miklós; Gadó, Krisztián; Horváth, Sándor; Vajda, István; Marcsa, Dániel; Belahcen, Anouar (Recent Innovations in Mechatronics, 2018)
Induction machines are popular in every segments of industry due to their simple construction and robust operation. Asynchronous machines have been being built in electric vehicles, too. The paper presents the two dimensional analysis of a voltage-fed induction machine by different kind of finite element software. The results have been compared.